The employer's legal handbook - Steingold, Fred S., 1936-2017 (Berkeley, California : Nolo, 2015)
Provides the information employers need to handle every aspect of the employment relationship, including hiring, performance reviews, benefits, and layoffs.
9. Workers with disabilities -- The Americans With Disabilities Act -- Businesses that are covered -- Who is protected -- Exceptions to coverage -- Providing reasonable accommodations -- Workers with emotional or mental impairments -- Financial assistance -- Health and safety standards -- Medical exams -- Enforcement -- 10. Termination -- Wrongful discharge cases -- Guarding against legal claims -- Guidelines for firing employees -- Investigating complaints against workers -- Alternatives to firing -- The firing process -- Heading off trouble -- Final paychecks -- Continuing health insurance -- Unemployment compensation -- Protecting your business information -- Handling postemployment inquiries -- 11. Employee privacy -- Monitoring employees at work -- Searches -- Employee dating -- Other off-duty activities -- 12. Independent contractors -- Comparing employees and independent contractors -- The IRS rules -- workers automatically classified as employees -- State laws -- The risks of misclassification -- Hiring independent contractors -- 13. Unions -- The National Labor Relations Act -- Unionizing a workplace -- Employer rights and limitations -- Employee rights and limitations -- Making unions unnecessary -- 14. Lawyers and legal research -- Getting help from a lawyer -- Paying a lawyer -- Resolving problems with your lawyer -- Legal research -- Appendix. Labor departments and agencies -- State drug and alcohol testing laws -- State laws on employee arrest and conviction records -- State laws on access to personnel records -- State minimum wage laws for tipped and regular employees -- State meal and rest break laws -- State health insurance continuation laws -- State family and medical leave laws -- State laws prohibiting discrimination in employment -- Agencies that enforce laws prohibiting discrimination in employment -- State laws that control final paychecks.
"Manage your employees & workplace effectively"--Cover.
Includes bibliographical references and index.
Keywords: Labor laws and legislation -- United States -- Popular works; Law for laypersons